Viajando os sertões: Nestor Lima e a territorialização das cidades sertanejas na obra "Municípios do Rio Grande do Norte" (1938-1942) - Dutra, Adalgisa Maria Alencar (2021)
This is a study on the process of territorialization of the Physiographic Zones – Zona do Rio Seridó and Zona do Rio Assú – based on the work Municípios do Rio Grande do Norte by Nestor dos Santos Lima. In this sense, we have considered its territorialization as a process of changes in the administrative and ecclesiastical scope, as an agent of change in the process of occupation of these Sertões. This process is considered since the characteristics of the Sertões and their singularities are portrayed. The Zona do Rio Seridó is characterized by the documentary sources researched by the author, as well as by the use of memories as a historical source. Based on Michel de Certeau (2002), we seek to analyze the historical context of the creation of the Instituto Histórico e Geográfico Brasileiro (IHGB) and the Instituto Histórico e Geográfico do Rio Grande do Norte (IHGRN), to understand the intellectual path of the author Nestor dos Santos Lima and, consequently, the ideological bases that resulted in his main work on the cities of Rio Grande do Norte. The Assú River Zone is portrayed from the cities that make up the region, in order to highlight the fauna, flora and the process of historical change. Methodologically, it started with the reading and bibliographic review, selection and composition of a picture of the cities and their respective zones, as well as a qualitative analysis of the work, in order to understand the historical process provided by the author. It was concluded that his writing process resulted from his institutional place as an agent of the state government, that the Sertões of Seridó and Assú were described in the historiography in order to emphasize the process of territorial changes, and that memory appears in the work that was the source of research.